2021
DOI: 10.1101/2021.05.07.443055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infection, recovery and re-infection of farmed mink with SARS-CoV-2

Abstract: Mink, on a farm with about 15,000 animals, became infected with SARS-CoV-2. Over 75% of tested animals were positive for SARS-CoV-2 RNA in throat swabs and 100% of tested animals were seropositive. The virus responsible had a deletion of nucleotides encoding residues H69 and V70 within the spike protein gene. The infected mink recovered and after free-testing of the mink, the animals remained seropositive. During follow-up studies, after a period of more than 2 months without virus detection, over 75% of teste… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Some mutations developed in mink farms and in 12 humans with COVID-19 who lived around the mink farms in Jutland included Y453F, D614G, isoleucine 692 to valine (I692V), and methionine 1229 to isoleucine (M1229I) [57]. The deletion of H69 and V70 within the spike gene occurred in mink farms probably as an adaptation of the virus to increase its binding ability to the receptor [114]. The same finding was revealed in Poland [115].…”
Section: Sars-cov-2 Infections In Minksmentioning
confidence: 70%
“…Some mutations developed in mink farms and in 12 humans with COVID-19 who lived around the mink farms in Jutland included Y453F, D614G, isoleucine 692 to valine (I692V), and methionine 1229 to isoleucine (M1229I) [57]. The deletion of H69 and V70 within the spike gene occurred in mink farms probably as an adaptation of the virus to increase its binding ability to the receptor [114]. The same finding was revealed in Poland [115].…”
Section: Sars-cov-2 Infections In Minksmentioning
confidence: 70%
“…To date, the only farmed animals that were tested positive following natural infection (detection of SARS‐CoV‐2 RNA by PCR) are mink (Molenaar et al, 2020; Oreshkova et al, 2020; Domańska‐Blicharz et al, 2021; EFSA, 2021; Hammer et al, 2021; Rabalski et al, 2021; Rasmussen et al, 2021), raccoon dogs (one outbreak reported in Poland in 2021), and to a certain extent also ferrets (Shi et al, 2020; Giner et al, 2021; Gortázar et al, 2021; Račnik et al, 2021). The former two species are bred mainly in the fur industry, while ferrets are bred mainly as companion, research or as work animals for rabbit hunting and rabbit control.…”
Section: Assessmentmentioning
confidence: 99%
“…The sequencing conducted in the isolates from Spain revealed that the most frequent lineage detected was B.1.1.7 (Alpha variant). The mutations identified were D614G, N501T (a site related to an adaptation to the host and to antigenic drift), A222V (characteristic of the human cases), Y453F (very rarely, detected in Galicia in March 2021 – described in samples from several Danish mink farms (Hammer et al, 2021; Rasmussen et al, 2021)), and F486V and D796H (the two changes that always appear together, detected in 2020).…”
Section: Assessmentmentioning
confidence: 99%
“…Additionally, within‐host adaptation in chronic infection and responses to selective pressure to evade the immune system may have also played a role in the emergence of VOCs (MacLean et al, 2021 ). Notably, a recent study reported the occurrence of SARS‐CoV‐2 infection, recovery and three months after, reinfection among 75% of tested mink in a Danish farm, possibly as a result of continued viral replication within susceptible hosts with access to the premises (Rasmussen et al, 2021 ). Although surveillance of VOCs to date has been almost exclusively directed at humans, convergent evolution of potentially harmful mutations can occur in different host species and later spill back to humans.…”
Section: Evolution Of Virulencementioning
confidence: 99%